2022
DOI: 10.1007/s00109-022-02189-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles-associated tRNA-derived fragments (tRFs): biogenesis, biological functions, and their role as potential biomarkers in human diseases

Abstract: Traditionally, transfer RNAs (tRNAs) specifically decoded messenger RNA (mRNA) and participated in protein translation. tRNA-derived fragments (tRFs), also known as tRNA-derived small RNAs (tsRNAs), are generated by the specific cleavage of pre- and mature tRNAs and are a class of newly defined functional small non-coding RNAs (sncRNAs). Following the different cleavage positions of precursor or mature tRNA, tRFs are classified into seven types, 5′-tRNA half, 3′-tRNA half, tRF-1, 5′U-tRF, 3′-tRF, 5′-tRF, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 119 publications
0
38
0
Order By: Relevance
“…The clinical significance of tRNAs and tRFs in EVs has recently been reviewed by Liu et al (2022) and Weng et al (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of tRNAs and tRFs in EVs has recently been reviewed by Liu et al (2022) and Weng et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for standardised nomenclature for the different tRFs to enable inter-study comparisons and metanalyses. The clinical significance of tRNAs and tRFs in EVs has recently been reviewed by Liu et al (2022) and Weng et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…This type of RNAs, tRNA-derived fragments, are generated by the cleavage of tRNAs. It has been demonstrated that tRNA-derived fragments in extracellular vesicles act as regulatory molecules in various cellular processes and have the potential to be biomarkers in human diseases 43 . SNORD118 was ranked as the fourth top-ranked candidate in all ex-RNAs for hESC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fib-iPSCs were obtained from Human Embryonic Stem Cell Core, Harvard Medical School. Fib-iPSCs were reprogrammed from fibroblasts, by George Q. Daley Lab (Children's Hospital Boston, MA) and have been well characterized and described in the literature [43]. For 2D cell culture, H9s and iPSCs were cultured in 6-welll plate coated with Matrigel (BD Biosciences, #354277) in Essential 8 TM medium (E8, Life Technologies, #A1517001).…”
Section: Methodsmentioning
confidence: 99%
“…The level of EVs in humans has gained attention for the early diagnosis of various diseases using liquid biopsy owing to their distribution in various body fluids, including blood, urine, saliva, spinal fluid, and tears, as well as their stability [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. As the amount and type of these functional molecules present within or on the surface of EVs vary depending on the disease, they could be used for disease diagnosis, prognosis, and therapeutic targets [ 108 , 109 , 110 , 111 , 112 , 113 , 114 <...…”
Section: Introductionmentioning
confidence: 99%